A Systematic Review of the Neuropathologic Findings of Post-Viral Olfactory Dysfunction: Implications and Novel Insight for the COVID-19 Pandemic. Issue 3 (May 2021) - Lee, Jason C.; Nallani, Rohit; Cass, Lauren; Bhalla, Vidur; Chiu, Alexander G.; Villwock, Jennifer A.
Background: Post-viral olfactory dysfunction is a common cause of both short- and long-term smell alteration. The coronavirus pandemic further highlights the importance of post-viral olfactory dysfunction. Currently, a comprehensive review of the neural mechanism underpinning post-viral olfactory dysfunction is lacking. Objectives: To synthesize the existing primary literature related to olfactory dysfunction secondary to viral infection, detail the underlying pathophysiological mechanisms, highlight relevance for the current COVID-19 pandemic, and identify high impact areas of future research. Methods: PubMed and Embase were searched to identify studies reporting primary scientific data on post-viral olfactory dysfunction. Results were supplemented by manual searches. Studies were categorized into animal and human studies for final analysis and summary. Results: A total of 38 animal studies and 7 human studies met inclusion criteria and were analyzed. There was significant variability in study design, experimental model, and outcome measured. Viral effects on the olfactory system varies significantly based on viral substrain but generally include damage or alteration in components of the olfactory epithelium and/or the olfactory bulb. Conclusions: The mechanism of post-viral olfactory dysfunction is highly complex, virus-dependent, and involves a combination of insults at multiple levels of the olfactory pathway. This will have important implications for future diagnostic and therapeutic developments for patients infected with COVID-19.